New study of the local gravity field of El Hierro (Canary Islands) - Benavent, M.; Arnoso, J.; Montesinos, F.G. (Física de la Tierra, 2005)
El Hierro island has been built-up at the from a classic triple armed rift system, being its subaerial morphology enhanced by large scale landsliding. The ridges are marked on the Island by frequently aligned faults and volcanic centres. Three volcanic cycles take part in its evolution: Old, Intermediate and Recent Series, which can be clearly separated. The Bouguer anomaly map in this island shows several gravity anomalies which can be associated to the different stages of its growth. Adetailed study, increasing the number of gravity stations and improving previous researches, has let us establish a better interpretation of the local gravity anomalies associated with the recent volcanism in the area. To remove the influence of the deepest sources of the gravity field in this local study, we identify a regional trend by a robust polynomial fit. The residual map is analyzed with statistical techniques. The observational noise is filtered distinguishing the signal corresponding to the local gravity field. The inversion of these data is based on a genetic algorithm which optimizes the model of distribution of gravity sources by emulating the Darwin’s principle about evolution. The geometry of these sources is determined upon a prismatic partition of the subsurface, and adopting a priori values of density contrasts. This local gravity study shows low-density bodies following the concentration of recent emission centres on El Hierro, and they conform the three-armed rift structure regularly developed in this island. The high density structures coincide where the oldest volcanism outcrops, just in the areas which suffered giant landslides.